Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.